Microbiota modulation for infectious complications following allogeneic hematopoietic stem cell transplantation in pediatric hematological malignancies - Dai, Wei; Chen, Xiaofan; Zhou, Huanhuan; Liu, Ning; Jin, Mengdi; Guo, Zhi (Frontiers in Pediatrics, 2025)
The intervention of microbiota modulation in the treatment of infection complications after allogeneic hematopoietic stem cell transplantation in pediatric patients with hematological malignancies has shown potential benefits. Through the use of probiotics, prebiotics, synbiotics, and fecal microbiota transplantation (FMT), these interventions modulate the gut microbiota and enhance immune function to prevent and treat infections. They have been shown to reduce the incidence of diarrhea and intestinal infections, mitigate the issue of antibiotic resistance, and promote the recovery of gut microbiota. Future research is needed to further assess the safety and efficacy of these interventions and to establish standardized treatment protocols.